Pembimbingan Pengembangan Bahan Ajar Berbasis Lintas Budaya pada Sekolah Menengah - Eripuddin; Rahayu, Pipit; Rasyidah, Ummi; Nurazimah Juhastri, Azi (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2025)
The intercultural learning guiding is necessary to introduce in teaching and learning process because the teacher and students to understand the multicultural context in the classroom. The participant of this study consists of the teacher and the students of SMAN 2 Rambah Hilir. This study was conducted by using some procedure such as introduction phase, training phase and implementing phase. The result shows that teachers also emphasize to students to continue learning, not only in the classroom, but also outside the classroom at home with friends or family. Thus, the guiding or this training provide the significance impact for understanding the intercultural learning. In this case, the teachers and students are expected to comprehend the implication of intercultural learning. It engages the motivation to elaborate the system of teaching and learning process.